Disobedience of The Constitutional Court’s Decision by The Supreme Court (Universitas Negeri Semarang, 2022)
The Constitutional Court as one of the institutions that exercises judicial function has a final and binding decision that binds all parties. However, in practice, the decisions of the Constitutional Court are often ignored by parties, one of which is the Supreme Court. There are several Supreme Court decisions that do not consider the decisions of the Constitutional Court. This demonstrates disobedience to legal norms that are final. This is the reason why the researcher wants to examine the constitutionality of the Supreme Court’s decision which does not consider the decision of the Constitutional Court, and what are the legal implications. This research is doctrinal research with a normative legal approach, that used secondary data obtained through literature study. Based on the results of the study, the decisions of the Supreme Court which do not consider the decisions of the Constitutional Court can be said to be unconstitutional, or it can be said that there has been a violation of the constitution because the decisions of the Constitutional Court represent the essence of the 1945 Constitution of the Republic of Indonesia. The legal implication obtained are the supreme court decision is still be act as jurisprudence; there is legal confusion and uncertainty regarding the conflicting decisions; the occurrence of constitutionalism justice delay; and can undermine the authority of the 1945 Constitution of the Republic of Indonesia.